Energy poverty: an overlooked determinant of health and climate resilience in Canada - Riva, Mylène; Kingunza Makasi, Sophie; O’Sullivan, Kimberley C.; Das, Runa R.; Dufresne, Philippe; Kaiser, David; Breau, Sébastien (Canadian Journal of Public Health, 2023)
Abstract Objective Despite Canada being an important energy producer, not all Canadians can access or afford adequate levels of energy services at home to meet their needs, maintain healthy indoor temperatures, and live a decent life—a situation known as energy poverty. Depending on the measure, 6–19% of Canadian households face energy poverty. Health risks associated with energy poverty are documented in countries with milder climates. This study explores, for the first time in the Canadian context, the association between energy poverty and health. Methods Cross-sectional data are from the 2018 Canadian Housing Survey. Analyses are conducted on a sample weighted to represent 14 million Canadian households. The associations between expenditure-based and self-reported measures of energy poverty and self-rated general and mental health were assessed using logistic regression models, adjusted for potential confounding variables. Results The odds of rating one’s general (OR: 1.48; 95%CI: 1.29, 1.70) and mental (OR: 1.21; 1.04, 1.41) health as poor are significantly higher for Canadian adults in households with a high share of energy expenditure to income. The likelihood of poor general and mental health was significantly higher for those dissatisfied with the energy efficiency of their dwelling, and with their ability to maintain a comfortable temperature both in the winter and in the summer. Conclusion Exposure to energy poverty is associated with significantly increased likelihood of poor general and mental health. Given the high proportion of Canadian households facing energy poverty, with demonstrated implications for population health, tackling energy poverty is essential for an equitable energy transition and for climate resilience. , Résumé Objectif Bien que le Canada soit un important producteur d’énergie, entre 6 % et 19 % des ménages canadiens, selon la mesure retenue, sont en précarité énergétique, une situation qui survient lorsqu’un ménage n’a pas les moyens ou l’accès à des services énergétiques résidentiels adéquats pour maintenir une température ambiante confortable, répondre à ses besoins et vivre dans la dignité. Les risques socio-sanitaires associés à la précarité énergétique sont documentés dans des pays au climat tempéré. Cette étude explore, pour la première fois dans le contexte canadien, l’association entre la précarité énergétique et la santé. Méthodes Les données transversales proviennent de l’Enquête canadienne sur le logement de 2018. Les associations entre différentes mesures de précarité énergétique (mesures basées sur les dépenses des ménages et auto-rapportées) et la santé générale et mentale perçue sont estimées à l’aide de modèles de régression logistique ajustés pour des variables de confusion potentielles. Les analyses sont réalisées sur un échantillon pondéré pour représenter 14 millions de ménages. Résultats Les probabilités de déclarer une mauvaise santé générale (OR : 1,48; IC95% : 1,29-1,70) et mentale (OR : 1,21; 1,04-1,41) sont significativement plus élevées pour les adultes canadiens dont le ménage consacre une part importante de son revenu aux coûts énergétiques. Elles sont aussi significativement plus élevées pour ceux qui déclarent être insatisfaits avec l’efficacité énergétique de leur logement et de leur capacité à maintenir une température confortable en hiver et en été. Conclusion Vivre en situation de précarité énergétique est associée à des probabilités accrues de déclarer une mauvaise santé générale et mentale chez les adultes canadiens. En raison de la proportion élevée de ménages canadiens confrontés à la précarité énergétique et des effets socio-sanitaires que cette situation engendre, lutter contre la précarité énergétique est essentiel pour une transition énergétique équitable et pour la résilience climatique.